"Do You Know How Much I Suffer?": How Young People Negotiate the Tellability of Their Mental Health Disruption in Anonymous Distress Narratives on Social Media. Issue 13 (10th November 2021) - Yeo, Tien Ee Dominic
ABSTRACT: The emergence of mental distress presents significant difficulties and dilemmas for adolescents and early adults about being open with their troubles and emotions. To better understand the communication practices and challenges that reflect the lived realities of marginalized youth struggling with mental health disruption, this study examines 136 anonymous personal stories disclosing self-harm behaviors or suicidal thoughts on a Facebook "secrets" page for Hong Kong students. The narrative analysis unveils young people's anecdotal accounts of hidden grievances and struggles around their mental distress, hitherto untold not because they are too difficult to tell but because they are too negative to be heard. Extending the concept of tellability, this study illustrates how anonymous distress storytelling on social media enables silenced and isolated distressed youth to resist the denial – invisibility, discredit, and mischaracterization – of their suffering by turning their disruptive experiences into stories worth telling through disclosure, clarification, and testimony. This study further clarifies the salient interpretive frameworks that shape young people's experience and communication of mental distress: the tyranny of happiness depicted to engender distress and languages of suffering used to resist culpability and plead for social respite. It highlights the disconnection in interpretations regarding the transitory nature of distress and its controllability as a major source of communication gap and interpersonal communication breakdowns. The findings call on health communication practices around mental health promotion to refrain from highlighting individual deficiencies or messages of positivity and speak out on the structural inconsistencies and communication denial that perpetuate and silence youth distress.